An empirical study of green management and performance in Taiwanese electronics firms - Ying-Chin Ho; Wen Bo Wang; Wen Ling Shieh (Cogent Business & Management, 2016)
Global warming and increased pollution from electronics production highlight the importance of green management (GM) for Taiwanese electronics firms. Through a survey of 213 Taiwanese electronics manufacturers, this study empirically examines the influence of GM on organizational performance improvement. Drawing on a moderated hierarchical regression analysis, we evaluate the general relationship between specific GM practices and performance. The findings indicate that GM has a significant impact on firm performance. We then investigate how contingency factors, circumstance uncertainty (CU), operation management philosophy, and total quality environmental management (TQEM) influence the relationship between GM practices and firm performance. Several crucial relationships are derived from our results. The moderating effects of CU and TQEM demonstrate that in some cases with certain GM practices, the inclusion or exclusion of CU and TQEM might reduce or improve performance. This study also discusses the managerial implications of the research results.
Keywords: 650